Gender, ethnicity and spiritual coping among bereaved HIV-positive individuals - Tarakeshwar, Nalini (Mental health, religion & culture, 2005)
We examined the influence of gender and ethnicity on coping strategies of 252 bereaved, HIV-positive individuals (65.1% male; 71% ethnic minorities [African-American and Hispanic]). Factor analyses of the Ways of Coping Questionnaire and Coping with Illness Scale yielded five coping subscales: Active, Avoidant, Social Support, Self-destructive, and Spiritual. Multivariate analyses of covariance revealed significant gender and ethnic group effects on spiritual coping, after controlling for social support, education, and sexual orientation. Of all subscales, only spiritual coping was not influenced by perceived social support. Women and ethnic minorities reported greater use of spiritual coping while White men reported the least use of spiritual coping. White women reported significantly greater use of avoidant coping than White men. Further, the relationship between spiritual coping and grief varied across gender and ethnicity. These results highlight the influence of gender and ethnicity in the use of spiritual coping and the importance of integrating spirituality in psychosocial interventions.